MODERN X-RAY DIAGNOSIS OF ADULT ACQUIRED FLATFOOT DEFORMITY - N. S. Serova; A. S. Belyaev; D. S. Bobrov; K. S. Ternovoy (Вестник рентгенологии и радиологии, 2017)
This scientific review is devoted to the modern diagnostics of adult flatfoot using radiographic method. Describes the main radiographic projections and basic morpho-functional parameters that determine the degree of deformation and the further tactics of patients’ treatment.